Stereoelectronic Effect of Protecting Groups on the Stability of Galactosyl Donor Intermediates - Ryan W. Kwok; Ryan Rutkoski; Pavel Nagorny; Mateusz Marianski (Molecules, 2025)
Using methods of DFT, we investigated the effect of electron withdrawing and electron donating groups on the relative stability of tentative glycosyl donor reaction intermediates. The calculation shows that by changing the stereoelectronic properties of the protecting group, we can influence the stability of the dioxolenium type of intermediates by up to 10 kcal mol−1, and that by increasing nucleophillicity of the 4-O-Bz group, the dioxolenium intermediate becomes more stable than a triflate–donor pair. We exploited this mechanism to design galactosyl donors with custom protecting groups on O2 and O4, and investigated the outcome of the reaction with cyclohexanol. The reaction showed no change in the product distribution, which suggests that the neighboring group participation takes precedence over remote group participation due to kinetic barriers.